Lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery

CN117691099BActive Publication Date: 2026-10-09BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311432321.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2026-10-09
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

[0006]本发明的目的是为了克服现有的富锂锰基正极材料的容量、首次效率和循环性能仍不佳的问题

Benefits of technology

[0019] (1) The lithium-rich manganese-based cathode material provided by the present invention is a secondary particle formed by the agglomeration of strip-shaped primary particles, and the secondary particles have open pores on the surface and a texture with three-dimensional channels inside; wherein, the proportion η of the primary particles in the surface clusters of the secondary particles satisfies: 5% ≤ η ≤ 30%; the average aspect ratio α of the primary particles satisfies: α ≥ 3; the cross-sectional porosity γ of the secondary particles satisfies: γ ≥ 5%; the average pore diameter d of the internal pores of the secondary particles... 50 Satisfy: 60nm≤d 50 ≤800nm. When the high aspect ratio primary particles on the surface of the lithium-rich manganese-based cathode material are arranged in different directions, open pores are formed between the primary particles and connected to the micropores inside the secondary particles, forming a three-dimensional channel for electrolyte flow. That is, through capillary force, the primary particles in the entire secondary particles can be completely immersed in the electrolyte, which allows lithium ions to diffuse in multiple directions of the grains. This is beneficial to increase the diffusion area of ​​lithium ions, shorten the diffusion path of lithium ions, and effectively improve the ionic conductivity and electronic conductivity of the lithium-rich manganese-based cathode material, thereby obtaining high capacity and first coulombic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117691099B_ABST
    Figure CN117691099B_ABST
Patent Text Reader

Abstract

This invention relates to the field of lithium-ion battery cathode materials, and discloses a lithium-rich manganese-based cathode material, its preparation method, and a lithium-ion battery. The cathode material is a secondary particle formed by the agglomeration of strip-shaped primary particles, and the secondary particles have open pores on their surface and a texture with three-dimensional channels inside; wherein: the proportion η of the primary particles in the surface clusters of the secondary particles satisfies: 5% ≤ η ≤ 30%; the average aspect ratio α of the primary particles satisfies: α ≥ 3; the cross-sectional porosity γ of the secondary particles satisfies: γ ≥ 5%; and the average pore diameter d of the internal pores of the secondary particles... 50 Satisfy: 60nm≤d 50 ≤800nm. This lithium-rich manganese-based cathode material, by controlling the arrangement and texture of primary particles, forms three-dimensional diffusion channels for lithium ions within the secondary particles. Furthermore, both primary and secondary particles meet the aforementioned specific parameter constraints, effectively improving the cathode material's capacity, initial efficiency, and cycle performance. Its process is simple and low-cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cathode materials for lithium-ion batteries, specifically to lithium-rich manganese-based cathode materials, their preparation methods, and lithium-ion batteries. Background Technology

[0002] Currently, lithium-ion batteries, as energy carriers with excellent comprehensive performance, are widely used in electric vehicles, energy storage power stations, communications, and digital electronic products. Among them, the cathode material, as the core and key component of lithium-ion batteries, directly determines the technical performance of the battery. Therefore, improving the performance of cathode materials is a research hotspot in the field of lithium-ion batteries, manifested in the modification of existing materials and the search for novel cathode materials with higher electrochemical capacity.

[0003] Currently, commercially available cathode materials mainly include layered LiMO2 (where M is Ni, Co, Mn, etc.), spinel-type LiMn2O4, and olivine-type LiFePO4. Layered LiNi 1-x-y Co x Mn y O2, due to the synergistic effect of Ni, Co, and Mn, reduces material costs and improves performance, but its typical specific capacity does not exceed 220 mAh / g. Spinel-structured LiMn2O4 is prone to crystal transformation, the Jahn-Teller effect, and manganese ion dissolution during cycling, leading to rapid capacity decay and poor cycle performance. Olivine-type LiFePO4 has a lower specific capacity, generally below 170 mAh / g. The commonly used anode material, graphite, has a specific capacity reaching 340 mAh / g; the relatively low specific capacity of cathode materials limits the development of lithium-ion batteries. Therefore, developing high-capacity cathode materials is of great significance to the development of lithium-ion batteries.

[0004] Lithium-rich manganese-based cathode materials have become a research hotspot in the field of lithium-ion battery cathodes due to their high specific capacity and high energy density. They can be considered as solid solutions of Li₂MnO₃ and LiMO₂. Containing low Ni and Co content and high Mn content, lithium-rich manganese-based cathode materials offer lower cost and better safety compared to layered LiMO₂. Their specific capacity exceeds 220 mAh / g, average voltage is higher than 3.5 V, and energy density is significantly higher than spinel-type LiMn₂O₄ and olivine-type LiFePO₄. Therefore, lithium-rich manganese-based cathode materials are considered a preferred material for next-generation lithium-ion battery cathodes.

[0005] Currently, the capacity, initial coulombic efficiency (CE), rate capability, and cycle performance of lithium-rich manganese-based cathode materials are obstacles to their commercialization. Existing technologies mainly achieve high capacity and CE by controlling the primary particle size or optimizing the Li content. However, these methods can only improve material performance to a small extent, and the improvement in rate capability and cycle performance is also minimal. Therefore, it is necessary to design material structures and synthesis routes to improve the capacity, CE, and cycle performance of lithium-rich manganese-based cathode materials. Summary of the Invention

[0006] The purpose of this invention is to overcome the problems of poor capacity, first-cycle efficiency, and cycle performance of existing lithium-rich manganese-based cathode materials.

[0007] To achieve the above objectives, the first aspect of the present invention provides a lithium-rich manganese-based cathode material, wherein the lithium-rich manganese-based cathode material is a secondary particle formed by the agglomeration of strip-shaped primary particles, and the secondary particles have open pores on their surface and a texture with three-dimensional channels inside; wherein:

[0008] The proportion η of primary particles in the surface clusters of secondary particles satisfies: 5% ≤ η ≤ 30%;

[0009] The average aspect ratio α of primary particles satisfies: α≥3;

[0010] The cross-sectional porosity γ of the secondary particles satisfies: γ≥5%;

[0011] The average pore diameter d of the internal pores of secondary particles 50 Satisfy: 60nm≤d 50 ≤800nm.

[0012] A second aspect of the present invention provides a method for preparing the lithium-rich manganese-based cathode material described in the first aspect, the method comprising the following steps:

[0013] (1) A nickel source, a cobalt source, a manganese source, a precipitant, and a complexing agent are contacted to carry out a co-precipitation reaction to obtain a precursor slurry; then the precursor slurry is sequentially subjected to pressure filtration, washing, drying, and sieving to obtain a precursor;

[0014] (2) In an oxygen-containing atmosphere, a mixture containing a lithium source and the precursor is subjected to a first sintering, and then crushed and sieved in sequence to obtain the sintered product.

[0015] (3) In an oxygen-containing atmosphere, the mixture containing the sintering process product is subjected to a second sintering and then sieved.

[0016] In step (2), the first sintering includes a stage I and a stage II performed sequentially, wherein the heating rate of stage I is greater than the heating rate of stage II.

[0017] A third aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery contains the lithium-rich manganese-based cathode material described in the first aspect.

[0018] Through the above technical solution, the present invention has the following advantages:

[0019] (1) The lithium-rich manganese-based cathode material provided by the present invention is a secondary particle formed by the agglomeration of strip-shaped primary particles, and the secondary particles have open pores on the surface and a texture with three-dimensional channels inside; wherein, the proportion η of the primary particles in the surface clusters of the secondary particles satisfies: 5% ≤ η ≤ 30%; the average aspect ratio α of the primary particles satisfies: α ≥ 3; the cross-sectional porosity γ of the secondary particles satisfies: γ ≥ 5%; the average pore diameter d of the internal pores of the secondary particles... 50 Satisfy: 60nm≤d 50 ≤800nm. When the high aspect ratio primary particles on the surface of the lithium-rich manganese-based cathode material are arranged in different directions, open pores are formed between the primary particles and connected to the micropores inside the secondary particles, forming a three-dimensional channel for electrolyte flow. That is, through capillary force, the primary particles in the entire secondary particles can be completely immersed in the electrolyte, which allows lithium ions to diffuse in multiple directions of the grains. This is beneficial to increase the diffusion area of ​​lithium ions, shorten the diffusion path of lithium ions, and effectively improve the ionic conductivity and electronic conductivity of the lithium-rich manganese-based cathode material, thereby obtaining high capacity and first coulombic efficiency.

[0020] Furthermore, the three-dimensional channels formed by the lithium-rich manganese-based cathode material can provide sufficient space for volume changes during charging and discharging of primary particles in high-voltage, high-discharge environments, thereby reducing stress between primary particles, reducing the probability of microcracks forming within the particles, and improving the cycle life of the cathode material.

[0021] In summary, the lithium-rich manganese-based cathode material can effectively improve the capacity, first-pass efficiency, and cycle performance of the cathode material by controlling the arrangement and texture of the primary particles and forming a three-dimensional diffusion channel for lithium ions inside the secondary particles, and by ensuring that the primary and secondary particles meet specific parameter constraints.

[0022] (2) The preparation method provided by the present invention is simple, the process is controllable, and the production cost is low, making it suitable for large-scale industrial production. Attached Figure Description

[0023] Figure 1 This is a scanning electron microscope image of the lithium-rich manganese-based cathode material prepared in Example 1 of this invention;

[0024] Figure 2 This is a cross-sectional view of the lithium-rich manganese-based cathode material prepared in Example 1 of the present invention;

[0025] Figure 3 This is a cross-sectional pore treatment diagram of the lithium-rich manganese-based cathode material prepared in Example 1 of the present invention;

[0026] Figure 4 This is a scanning electron microscope image of the positive electrode material prepared in Comparative Example 1 of the present invention;

[0027] Figure 5 This is a comparison of the charge-discharge curves of the lithium-rich manganese-based cathode materials prepared in Example 1 and Comparative Example 1 of this invention at 0.1C.

[0028] Figure 6 This is a comparison chart of the cycle performance of the lithium-rich manganese-based cathode materials prepared in Example 1 and Comparative Example 1 of this invention at 0.5C. Detailed Implementation

[0029] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0030] In this invention, unless otherwise specified, "first" and "second" do not represent a sequence or limit the materials or operations, but are only used to distinguish between the materials or operations. For example, "first" and "second" in "first sintering" and "second sintering" are only used to distinguish them to indicate that they are not the same sintering operation.

[0031] In this invention, unless otherwise specified, room temperature refers to 25±2℃.

[0032] As previously stated, the first aspect of this invention provides a lithium-rich manganese-based cathode material, wherein the lithium-rich manganese-based cathode material is a secondary particle formed by the agglomeration of strip-shaped primary particles, and the secondary particles have open pores on their surface and a texture with three-dimensional channels inside; wherein:

[0033] The proportion η of primary particles in the surface clusters of secondary particles satisfies: 5% ≤ η ≤ 30%;

[0034] The average aspect ratio α of primary particles satisfies: α≥3;

[0035] The cross-sectional porosity γ of the secondary particles satisfies: γ≥5%;

[0036] The average pore diameter d of the internal pores of secondary particles 50 Satisfy: 60nm≤d 50 ≤800nm.

[0037] The proportion (η) of primary particles in the surface clusters of secondary particles is defined as follows: a surface cluster refers to a cluster with two or more adjacent primary particles, and the length of the shared grain boundary is greater than or equal to half the length of the longer of the adjacent particles. Three SEM images of the surface morphology of secondary particles are randomly selected, and the ratio of the number of primary particles contained in the surface clusters in each SEM image to the total number of primary particles in that image is calculated. The average value is then taken as the proportion of primary particles in the surface clusters of secondary particles.

[0038] The aspect ratio of a primary particle is the quotient of its length and its width perpendicular to the length direction (e.g., ...). Figure 1 For the L / W shown, three SEM images of the secondary particle surface morphology are randomly selected, where the number of primary particles shown is ≥100. The aspect ratio of the primary particles in the images is measured, and the average value is calculated. This average aspect ratio α of the primary particles in the material is the average aspect ratio α of the primary particles.

[0039] Cross-sectional porosity (γ) of secondary particles: Measured by scanning electron microscopy (SEM), a complete particle with a diameter of (0.9-1.1)×D was observed in the SEM. 50 The cross-section of the particles is analyzed. The number of pixels with holes in the three particle cross-sections is counted and divided by the total number of pixels in the three particles. The area ratio of the holes in the cross-section is calculated, which is the cross-sectional porosity of the secondary particles.

[0040] The average pore diameter d of the internal pores of the secondary particles 50 The results were obtained using the mercury porosimetry method, specifically according to the national standard GB / T 21650.1-2008 "Mercury Porosimetry and Gas Adsorption Method for the Determination of Pore Size Distribution and Porosity of Solid Materials - Part 1: Mercury Porosimetry".

[0041] During their research, the inventors of this invention discovered that lithium-rich manganese-based cathode materials with the above-mentioned specific structure, through the structural control of specific primary and secondary particles, and with the primary and secondary particles satisfying the above-mentioned specific parameter limitations, can effectively improve the capacity, initial coulombic efficiency, and cycle performance of the cathode material.

[0042] According to some embodiments of the present invention, preferably, the proportion η of primary particles in the surface clusters of secondary particles satisfies: 10% ≤ η ≤ 28%, and more preferably satisfies: 13% ≤ η ≤ 25%.

[0043] According to some embodiments of the present invention, preferably, the average aspect ratio α of the primary particles satisfies: α≥4.

[0044] According to some embodiments of the present invention, preferably, the cross-sectional porosity γ of the secondary particles satisfies: γ≥10%.

[0045] According to some embodiments of the present invention, preferably, the average pore diameter d of the internal pores of the secondary particles is... 50 Satisfy: 100nm≤d 50 ≤600nm, preferably satisfying: 140nm≤d 50 ≤400nm.

[0046] The parameters of the primary and secondary particles are limited to the above-mentioned preferred range, which is beneficial to further improve the capacity, initial coulombic efficiency and cycle performance of the cathode material.

[0047] According to some embodiments of the present invention, preferably, the average particle size D of the secondary particles is... 50 It is 5-15μm.

[0048] According to some embodiments of the present invention, preferably, the lithium-rich manganese-based cathode material has the composition shown in Formula I:

[0049] Li z (Ni x Co y Mn 1-x-y-m M 1 m M 2 n )O u N w Formula I;

[0050] Wherein, 1.30≤z≤1.50, 0.25≤x≤0.45, 0≤y≤0.10, 0≤m≤0.05, 0≤n≤0.05, 2.20≤u≤2.60, 0≤w≤0.09;

[0051] M 1 Selected from at least one of Al, Zr, Y, Mg, Ti, W, Si, Yb, Nb, Sc, La, Sr, Sm and Ta;

[0052] M 2 Selected from at least one of B, Mg, Al, Ti, V, Sr, Y, Zr, Nb, Mo, Sc, Cr, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and W;

[0053] N is selected from at least one of F, S, Cl and P.

[0054] According to some embodiments of the present invention, preferably, in formula I, 1.30≤z≤1.45, 0.30≤x≤0.40; more preferably, 1.33≤z≤1.40, 0.30≤x≤0.37.

[0055] According to some embodiments of the present invention, preferably, 0.001≤m≤0.03, 0.001≤n≤0.03; more preferably, 0.002≤m≤0.02, 0.002≤n≤0.02.

[0056] A second aspect of the present invention provides a method for preparing the lithium-rich manganese-based cathode material described in the first aspect, the method comprising the following steps:

[0057] (1) A nickel source, a cobalt source, a manganese source, a precipitant, and a complexing agent are contacted to carry out a co-precipitation reaction to obtain a precursor slurry; then the precursor slurry is sequentially subjected to pressure filtration, washing, drying, and sieving to obtain a precursor;

[0058] (2) In an oxygen-containing atmosphere, a mixture containing a lithium source and the precursor is subjected to a first sintering, and then crushed and sieved in sequence to obtain the sintered product.

[0059] (3) In an oxygen-containing atmosphere, the mixture containing the sintering process product is subjected to a second sintering and then sieved.

[0060] In step (2), the first sintering includes a stage I and a stage II performed sequentially, wherein the heating rate of stage I is greater than the heating rate of stage II.

[0061] According to some embodiments of the present invention, preferably, in step (1), the conditions for the coprecipitation reaction include: a reaction pH of 9-11, preferably 9.5-10.5; a reaction temperature of 50-70℃, preferably 55-65℃; a reaction time of 30-50h; and a stirring speed of 100-300rpm.

[0062] According to some embodiments of the present invention, in step (1), the nickel source, the cobalt source, and the manganese source can be soluble nickel sources, soluble cobalt sources, and soluble manganese sources conventionally used in the art, and there are no particular limitations thereto. Preferably, the nickel source, the cobalt source, and the manganese source are at least one of sulfates, nitrates, and chlorides containing Ni, Co, and Mn. For example, the nickel source can be selected from at least one of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate; the cobalt source can be selected from at least one of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate; and the manganese source can be selected from at least one of manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate.

[0063] According to some embodiments of the present invention, preferably, in step (1), the contacting step includes: introducing a mixed salt aqueous solution containing the nickel source, the cobalt source, and the manganese source, the precipitant, and the complexing agent into a reaction vessel in a parallel flow. More preferably, the concentration of the mixed salt aqueous solution is 1-3 mol / L. The mixed salt aqueous solution can be commercially available or prepared according to conventional methods in the art, and there are no particular limitations in this regard. Further preferably, the contact is carried out under the protection of an inert gas.

[0064] According to some embodiments of the present invention, preferably, in step (1), the precipitant is at least one selected from NaOH, KOH, and LiOH. Preferably, the precipitant is provided in the form of an aqueous precipitant solution; preferably, the concentration of the aqueous precipitant solution is 1-6 mol / L.

[0065] According to some embodiments of the present invention, in step (1), the complexing agent can be a complexing agent conventionally used in the art, and there are no particular limitations thereto. Preferably, the complexing agent is at least one selected from ammonia, ammonium citrate, and ammonium sulfate. Preferably, the complexing agent is provided in the form of an aqueous solution of the complexing agent; preferably, the concentration of the aqueous solution of the complexing agent is 2-10 mol / L.

[0066] According to some embodiments of the present invention, in step (1), there is no particular limitation on the amount of the precipitant and the complexing agent, as long as the amount of the precipitant and the amount of the complexing agent are such that the coprecipitation reaction meets the growth requirements of the precursor.

[0067] According to some embodiments of the present invention, preferably, in step (1), the average particle size D of the precursor is... 50 It is 5-15μm.

[0068] According to some embodiments of the present invention, in step (2), the lithium source can be any lithium source known in the art suitable for preparing cathode materials, and there are no particular limitations thereto, all of which can achieve the inventive purpose of the present invention to a certain extent. Preferably, the lithium source is lithium carbonate and / or lithium hydroxide.

[0069] According to some embodiments of the present invention, preferably, in step (2), the mixture further includes a dopant, the dopant being a dopant containing M. 1 It contains at least one of the following: oxides, chlorides, sulfides, fluorides, hydroxides, and carbonates.

[0070] According to some embodiments of the present invention, preferably, in step (2), the molar amounts of the lithium source, the precursor, and the dopant satisfy: M 1 / (Ni+Co+Mn)=0-0.05, preferably 0.001-0.03, more preferably 0.002-0.02; Li / (Ni+Co+Mn+M 1 = 1.3-1.5; wherein, the lithium source is calculated as Li, the precursor is calculated as the total molar amount of Ni, Co, and Mn, and the dopant is calculated as M 1 count.

[0071] According to some embodiments of the present invention, preferably, in step (2), the conditions of stage I include: heating rate < 8℃ / min, preferably 1-7.5℃ / min; sintering temperature of 400-600℃; and holding time of 4-8 hours, preferably 5-7 hours.

[0072] According to some embodiments of the present invention, preferably, in step (2), the conditions of stage II include: a heating rate of 0.5-5℃ / min, preferably 1-3℃ / min; a sintering temperature of 750-950℃, preferably 800-900℃; and a holding time of 6-15 hours, preferably 8-10 hours.

[0073] According to some embodiments of the present invention, preferably, in step (2), the average particle size D of the sintered product is... 50 It is 5-15μm.

[0074] According to some embodiments of the present invention, preferably, in step (3), the mixture further includes a coating agent, the coating agent being a mixture containing M 2 It contains at least one of the following: oxides, chlorides, sulfides, fluorides, hydroxides, hydroxy oxides, and carbonates.

[0075] According to some embodiments of the present invention, preferably, in step (3), the molar amount of the coating agent satisfies: M 2 / (Ni+Co+Mn+M 1 The value is 0-0.05, preferably 0.001-0.03, and more preferably 0.002-0.02.

[0076] According to some embodiments of the present invention, preferably, in step (3), the conditions for the second sintering include: a sintering temperature of 300-750°C and a sintering time of 6-10 hours.

[0077] According to some embodiments of the present invention, preferably, the oxygen content in the oxygen-containing atmosphere is 20-100% by volume. Preferably, the oxygen-containing atmosphere is provided by air and / or 100% by volume oxygen.

[0078] According to some embodiments of the present invention, the pressure filtration, washing, and drying can be carried out using conventional methods well known to those skilled in the art, and there are no particular limitations thereto.

[0079] According to some embodiments of the present invention, the crushing and screening can be carried out using conventional methods well known to those skilled in the art, and there are no particular limitations, as long as D can be obtained. 50 Any product that meets the above requirements is acceptable.

[0080] A third aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery contains the lithium-rich manganese-based cathode material described in the first aspect.

[0081] Unless otherwise specified, all raw materials used in the following examples and comparative examples are commercially available products.

[0082] In the following examples and comparative examples, the relevant parameters were obtained through testing using the following methods:

[0083] 1. Particle size testing: A Malvern 2000 laser particle size analyzer purchased from Malvern Corporation was used for particle size analysis. 50 The test medium was deionized water with a refractive index of 1.74.

[0084] 2. Surface morphology of secondary particles: These were measured using a Hitachi S4800 scanning electron microscope. During the test, particles with a diameter of (0.9-1.1) × D were selected. 50 The surface morphology of the particles was tested by magnification 30,000 times.

[0085] 3. Average aspect ratio (α) of primary particles: The aspect ratio of a primary particle is the quotient of the length of a single primary particle and its width perpendicular to the length direction (e.g., ...). Figure 1 (L / W shown in the figure) Randomly select 3 SEM images of the surface morphology of secondary particles, where the number of primary particles shown is ≥100. Measure the aspect ratio of the primary particles in the images and calculate the average value, which is the average aspect ratio of the primary particles of the material.

[0086] 4. Proportion of primary particles in the surface clusters of secondary particles (η): A surface cluster refers to a cluster with two or more adjacent primary particles and a common grain boundary whose length is greater than or equal to half the length of the longer of the adjacent particles. Three SEM images of the surface morphology of secondary particles are randomly selected, showing at least 100 primary particles. The ratio of the number of primary particles in the surface clusters to the total number of primary particles in the image is calculated, and the average value is taken as the proportion of primary particles in the surface clusters of secondary particles.

[0087] 5. Cross-sectional porosity (γ) of secondary particles: Scanning electron microscopy (SEM) revealed a complete particle with a diameter of (0.9-1.1)×D. 50 The cross-section of the particles is analyzed. The number of pixels with holes in the SEM of the three particle cross-sections is counted and divided by the total number of pixels of the three particles. The area ratio of the cross-section holes is calculated, which is the cross-sectional porosity of the secondary particles.

[0088] 6. Average pore diameter (d) of the internal pores of secondary particles 50 The average pore diameter d of the internal pores of powder was measured using the mercury porosimetry method. 50 Specifically, the national standard GB / T 21650.1-2008, "Determination of Pore Size Distribution and Porosity of Solid Materials by Mercury Intrusion Porosimetry and Gas Adsorption Method - Part 1: Mercury Intrusion Porosimetry", was adopted.

[0089] 7. Electrochemical performance testing:

[0090] Battery Assembly: 9.0g of the positive electrode material, 0.5g of acetylene black, 0.5g of polyvinylidene fluoride (PVDF), and an appropriate amount of N-methylpyrrolidone (NMP) prepared in the examples and comparative examples were mixed to form a uniform slurry. The slurry was coated on aluminum foil and dried. Then, it was pressed into a positive electrode sheet with a diameter of 12mm and a thickness of 120μm under a pressure of 100MPa. The positive electrode sheet was then placed in a vacuum drying oven and dried at 120℃ for 12h. The negative electrode used a Li metal sheet with a diameter of 17mm and a thickness of 1mm. The separator used a polyethylene porous membrane with a thickness of 25μm. The electrolyte used was a mixture of equal amounts of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiPF6 as the electrolyte.

[0091] The positive electrode, separator, negative electrode, and electrolyte were assembled into a 2025 type button cell in an Ar gas glove box with a water content and oxygen content of less than 5 ppm. The electrochemical performance of the above button cell was tested, and the test results are listed in Table 3.

[0092] The definitions of capacity, coulombic efficiency, and cycle performance are as follows:

[0093] The initial discharge specific capacity was determined by placing the button cell for 2 hours after fabrication, allowing the open-circuit voltage to stabilize, charging the positive electrode to a cutoff voltage of 4.6V at a current density of 25mA / g, then charging at a constant voltage for 30 minutes, followed by discharging at the same current density to a cutoff voltage of 2.0V. This process was repeated once more, and the resulting battery was considered an activated battery. The ratio of discharge capacity to charge capacity is the coulombic efficiency.

[0094] Cyclic performance tests were conducted as follows: using activated batteries, the capacity retention of the material was examined by cycling 80 times at a current density of 0.5C (125mA / g) in a voltage range of 2-4.6V and a temperature of 25℃.

[0095] The following examples illustrate the lithium-rich manganese-based cathode material and its preparation method provided by the present invention.

[0096] Example 1

[0097] (1) A nickel source, cobalt source, manganese source, precipitant, and complexing agent are contacted to undergo a co-precipitation reaction to obtain a precursor slurry; then, the above precursor slurry is sequentially subjected to pressure filtration, washing, drying, and sieving to obtain the precursor; wherein:

[0098] The nickel source was nickel sulfate; the cobalt source was cobalt sulfate; the manganese source was manganese sulfate; the molar ratio of Ni:Co:Mn is shown in Table 1;

[0099] The complexing agent is provided in the form of an aqueous solution of ammonia, and the concentration is shown in Table 1.

[0100] The precipitant is provided in the form of an aqueous precipitant solution, the types of which are shown in Table 1, and the concentration is 2 mol / L;

[0101] The contact process is as follows: Under the protection of nitrogen, a mixed salt aqueous solution (100L, the concentration of which is shown in Table 1) containing the above-mentioned nickel source, cobalt source and manganese source, an aqueous solution of complexing agent and an aqueous solution of precipitant are introduced into the reactor in a parallel flow.

[0102] The conditions for the coprecipitation reaction are shown in Table 1; the drying temperature was 105℃.

[0103] The chemical formula and D of the obtained nickel-cobalt-manganese ternary precursor 50 See Table 2;

[0104] (2) In an oxygen-containing atmosphere, a mixture containing a lithium source, dopant, and the above-mentioned precursor is subjected to a first sintering, followed by crushing and sieving to obtain the sintered product; wherein:

[0105] The first sintering process consists of two stages, Stage I and Stage II, performed sequentially:

[0106] Stage I consists of heating from room temperature to sintering temperature T1 at a rate of V1 and holding time of t1.

[0107] Stage II is: the temperature is increased from the sintering temperature T1 of Stage I to the sintering temperature T2 of Stage II, the heating rate is V2, and the holding time is t2;

[0108] The types of lithium source and dopant, the amount of each raw material, the type of oxygen-containing atmosphere, and the conditions for the first sintering are shown in Table 1.

[0109] Before crushing and screening, the product from the first sintering is naturally cooled to room temperature.

[0110] The chemical composition and D of the sintered product obtained 50 See Table 2;

[0111] (3) In an oxygen-containing atmosphere, the mixture containing the coating agent and the above-mentioned sintering product is subjected to a second sintering and then sieved; wherein:

[0112] The types of coating agents and the amounts of each raw material are shown in Table 1;

[0113] The types of oxygen-containing atmospheres and the conditions for the second sintering are shown in Table 1;

[0114] Before sieving, the product from the second sintering is allowed to cool naturally to room temperature.

[0115] The chemical formula and D of the obtained lithium-rich manganese-based cathode material 50 See Table 2.

[0116] Examples 2-7

[0117] Following the method of Example 1, with the differences shown in Table 1, all other aspects were the same, and lithium-rich manganese-based cathode materials were prepared.

[0118] The chemical formula composition and characteristic parameter test data of each product during the preparation process are shown in Table 2.

[0119] Comparative Example 1

[0120] The method of Example 1 is followed, except that in step (2), the first sintering is a single stage, specifically: the temperature is raised from room temperature to the sintering temperature at a rate of 10℃ / min, the sintering temperature is 850℃, and the holding time is 8 hours; all other steps are the same, and the cathode material is obtained. The chemical composition and characteristic parameter test data of each product during the preparation process are shown in Table 2.

[0121] Comparative Example 2

[0122] The method is the same as in Example 1, except that in step (2), Li / (Ni+Co+Mn+M 1 The ratio of 1.60 to 1.60 was used; all other parameters were the same, resulting in the positive electrode material. The chemical composition and characteristic parameter test data of each product during the preparation process are shown in Table 2.

[0123] Comparative Example 3

[0124] The method is the same as in Example 1, except that in step (2), the first sintering is performed sequentially in stages I and II, wherein:

[0125] Stage I consists of: heating from room temperature to sintering temperature at a rate of 6°C / min; sintering temperature of 700°C; and holding time of 10 hours.

[0126] Stage II is as follows: the sintering temperature of Stage I is increased to the sintering temperature of Stage II at a rate of 6℃ / min; the sintering temperature of Stage II is 850℃; and the holding time is 8 hours.

[0127] The rest were the same, and the cathode material was obtained. The chemical composition and characteristic parameter test data of each product during the preparation process are shown in Table 2.

[0128] Comparative Example 4

[0129] The method is the same as in Example 1, except that in step (2), the first sintering is performed in two stages, I and II, in sequence, wherein the heating rate of stage I is less than the heating rate of stage II, that is:

[0130] Stage I consists of: heating from room temperature to sintering temperature at a rate of 2℃ / min; sintering temperature of 500℃; and holding time of 6 hours.

[0131] Stage II is as follows: the sintering temperature of Stage I is increased to the sintering temperature of Stage II at a rate of 5℃ / min; the sintering temperature of Stage II is 850℃; and the holding time is 8 hours.

[0132] The rest were the same, and the cathode material was obtained. The chemical composition and characteristic parameter test data of each product during the preparation process are shown in Table 2.

[0133] Comparative Example 5

[0134] The method is the same as in Example 1, except that in step (2), the first sintering is performed sequentially in stages I and II, wherein:

[0135] Stage II consists of heating from the sintering temperature of Stage I to the sintering temperature of Stage II at a rate of 2℃ / min; the sintering temperature of Stage II is 700℃; and the holding time is 4 hours.

[0136] The rest were the same, and the cathode material was obtained. The chemical composition and characteristic parameter test data of each product during the preparation process are shown in Table 2.

[0137] Comparative Example 6

[0138] The method is the same as in Example 1, except that in step (1), the precipitant is sodium carbonate; the conditions for the coprecipitation reaction are: the reaction pH is 8; the reaction time is 18h.

[0139] The rest were the same, and the cathode material was obtained. The chemical composition and characteristic parameter test data of each product during the preparation process are shown in Table 2.

[0140] Table 1

[0141]

[0142]

[0143] Note: The proportions of each element are expressed in molar ratios;

[0144] The concentration of the aqueous solution* refers to the concentration of the mixed salt solution containing nickel, cobalt, and manganese sources.

[0145] Table 1 (continued)

[0146]

[0147]

[0148] Note: The proportions of each element are expressed in molar ratios;

[0149] The concentration of the aqueous solution* refers to the concentration of the mixed salt solution containing nickel, cobalt, and manganese sources.

[0150] Test case

[0151] (1) Morphological test

[0152] The present invention tested scanning electron microscope (SEM) images of the cathode materials prepared in the above embodiments and comparative examples, wherein, Figure 1 This is a SEM image of the lithium-rich manganese-based cathode material prepared in Example 1 of this invention; Figure 2 This is a cross-sectional view of the lithium-rich manganese-based cathode material prepared in Example 1 of the present invention; Figure 3 This is a cross-sectional pore treatment diagram of the lithium-rich manganese-based cathode material prepared in Example 1 of the present invention; Figure 4 This is a SEM image of the cathode material prepared in Comparative Example 1 of the present invention. As can be seen from the image, the lithium-rich manganese-based cathode material obtained in Example 1 of the present invention consists of secondary particles formed by the agglomeration of strip-shaped primary particles. The secondary particles have open pores on their surface and a three-dimensional channel texture inside. In contrast, the cathode material obtained in Comparative Example 1 does not have open pores on its surface, and its primary particles do not have obvious strip-shaped features.

[0153] (2) Physical property testing

[0154] This invention tested the D of the cathode materials prepared in the above embodiments and comparative examples, as well as the intermediate products in the preparation process. 50 The proportion of primary particles in the surface clusters of secondary particles η, the average aspect ratio of primary particles α, the cross-sectional porosity of secondary particles γ, and the average pore size d of the internal pores of secondary particles.50 The specific test results are shown in Table 2.

[0155] Table 2

[0156]

[0157] Note: Process product* refers to the sintering process product; cathode material** refers to the lithium-rich manganese-based cathode material prepared in the examples or the cathode material prepared in the comparative examples.

[0158] Table 2 (continued)

[0159]

[0160]

[0161] Note: Process product* refers to the sintering process product; cathode material** refers to the lithium-rich manganese-based cathode material prepared in the examples or the cathode material prepared in the comparative examples.

[0162] Table 2 (continued)

[0163]

[0164] Note: Process product* refers to the sintering process product; cathode material** refers to the lithium-rich manganese-based cathode material prepared in the examples or the cathode material prepared in the comparative examples.

[0165] Table 2 (continued)

[0166]

[0167] Note: Process product* refers to the sintering process product; cathode material** refers to the lithium-rich manganese-based cathode material prepared in the examples or the cathode material prepared in the comparative examples.

[0168] (3) Electrochemical performance testing

[0169] The electrochemical performance of the cathode materials prepared in the above embodiments and comparative examples was tested, including 0.1C charge specific capacity, 0.1C discharge specific capacity, coulombic efficiency, and cycle performance (capacity retention). Specific test results are shown in Table 3, where:

[0170] This invention provides, by way of example, a comparison of charge-discharge curves of lithium-rich manganese-based cathode materials prepared in Example 1 and Comparative Example 1 at 0.1C, as shown in the figure. Figure 5 As shown; and a comparison graph of the cycling performance of the lithium-rich manganese-based cathode materials prepared in Example 1 and Comparative Example 1 at 0.5C, as shown. Figure 6 As shown in the figure, compared with Comparative Example 1, the battery assembled from the lithium-rich manganese-based cathode material prepared in Example 1 of the present invention has superior capacity, initial efficiency, and cycle performance.

[0171] The test results for the remaining embodiments and comparative examples are shown in Table 3.

[0172] Table 3

[0173]

[0174] The results above show that the battery assembled using the lithium-rich manganese-based cathode material provided by this invention has superior capacity, initial efficiency, and cycle performance.

[0175] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A lithium-rich manganese-based cathode material, characterized in that, The lithium-rich manganese-based cathode material is a secondary particle formed by the agglomeration of strip-shaped primary particles, and the surface of the secondary particles has open pores and a three-dimensional channel texture inside; wherein: The proportion of primary particles in the surface clusters of secondary particles η Satisfy: 5% ≤ η ≤30%; the surface cluster refers to a cluster of two or more adjacent primary particles, and the length of the common grain boundary is greater than or equal to half the length of the longer of the adjacent particles; the proportion η is obtained by randomly selecting three SEM images of the surface morphology of secondary particles, calculating the ratio of the number of primary particles contained in the surface cluster to the total number of primary particles in the images, and then calculating the average value. Average aspect ratio of primary particles α satisfy: α ≥3; Cross-sectional porosity of secondary particles γ satisfy: γ ≥5%; Average pore size of the internal pores of secondary particles d 50 Satisfy: 60nm≤ d 50 ≤800nm.

2. The lithium-rich manganese-based cathode material according to claim 1, wherein, The proportion of primary particles in the surface clusters of secondary particles η Satisfy: 10% ≤ η ≤28%.

3. The lithium-rich manganese-based cathode material according to claim 2, wherein, The proportion of primary particles in the surface clusters of secondary particles η Satisfying: 13%≤ η ≤25%.

4. The lithium-rich manganese-based cathode material according to claim 1, wherein, Average aspect ratio of primary particles α satisfy: α ≥4.

5. The lithium-rich manganese-based cathode material according to claim 1, wherein, Cross-sectional porosity of secondary particles γ satisfy: γ ≥10%.

6. The lithium-rich manganese-based cathode material according to claim 1, wherein, Average pore size of the internal pores of secondary particles d 50 Satisfy: 100nm≤ d 50 ≤600nm.

7. The lithium-rich manganese-based cathode material according to claim 6, wherein, Average pore size of the internal pores of secondary particles d 50 Satisfy: 140nm≤ d 50 ≤400nm.

8. The lithium-rich manganese-based cathode material according to claim 1, wherein, The average particle size D of the secondary particles 50 It is 5-15μm.

9. The lithium-rich manganese-based cathode material according to any one of claims 1-8, wherein, The lithium-rich manganese-based cathode material has the composition shown in Formula I: Li z (Ni x Co y Mn 1-x-y-m M 1 m M 2 n )O u N w Formula I; Among them, 1.30≤ z≤ 1.50, 0.25≤ x≤ 0.45, 0≤ y≤ 0.10, 0≤ m≤ 0.05, 0≤ n≤ 0.05, 2.20≤ u ≤2.60, 0≤ w ≤0.09; M 1 Selected from at least one of Al, Zr, Y, Mg, Ti, W, Si, Yb, Nb, Sc, La, Sr, Sm and Ta; M 2 Selected from at least one of B, Mg, Al, Ti, V, Sr, Y, Zr, Nb, Mo, Sc, Cr, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and W; N is selected from at least one of F, S, Cl and P.

10. The lithium-rich manganese-based cathode material according to claim 9, wherein, In Equation I, 1.30 ≤ z ≤1.45, 0.30≤ x ≤0.

40.

11. The lithium-rich manganese-based cathode material according to claim 10, wherein, 1.33≤ z ≤1.40,0.30≤ x ≤0.37。 12. The lithium-rich manganese-based cathode material according to claim 9, wherein, 0.001≤ m ≤0.03,0.001≤ n ≤0.03。 13. The lithium-rich manganese-based cathode material according to claim 12, wherein, 0.002≤ m ≤0.02,0.002≤ n ≤0.02。 14. A method for preparing a lithium-rich manganese-based cathode material according to any one of claims 1-13, the method comprising the following steps: (1) A nickel source, a cobalt source, a manganese source, a precipitant and a complexing agent are contacted to carry out a co-precipitation reaction to obtain a precursor slurry; then the precursor slurry is subjected to pressure filtration, washing, drying and sieving in sequence to obtain a precursor; (2) In an oxygen-containing atmosphere, a mixture containing a lithium source and the precursor is subjected to a first sintering, and then crushed and sieved in sequence to obtain the sintered product; (3) In an oxygen-containing atmosphere, the mixture containing the sintering process product is subjected to a second sintering and then sieved; in, In step (2), the first sintering includes a stage I and a stage II performed sequentially, wherein the heating rate of stage I is greater than the heating rate of stage II.

15. The preparation method according to claim 14, wherein, In step (1), the conditions for the coprecipitation reaction include: a reaction pH of 9-11; a reaction temperature of 50-70℃; a reaction time of 30-50h; and a stirring speed of 100-300rpm.

16. The preparation method according to claim 15, wherein, The conditions for the coprecipitation reaction include: a reaction pH of 9.5-10.5 and a reaction temperature of 55-65℃.

17. The preparation method according to claim 14, wherein, In step (1), the nickel source, the cobalt source, and the manganese source are at least one of sulfate, nitrate, and chloride salts containing Ni, Co, and Mn; The precipitant is at least one of NaOH, KOH, and LiOH; The complexing agent is at least one of ammonia, ammonium citrate, and ammonium sulfate.

18. The preparation method according to claim 14, wherein, In step (1), the average particle size D of the precursor is... 50 It is 5-15μm.

19. The preparation method according to any one of claims 14-18, wherein, In step (2), the lithium source is lithium carbonate and / or lithium hydroxide.

20. The preparation method according to any one of claims 14-18, wherein, In step (2), the mixture further includes a dopant, the dopant being a dopant containing M. 1 It contains at least one of the following: oxides, chlorides, sulfides, fluorides, hydroxides, and carbonates.

21. The preparation method according to claim 20, wherein, In step (2), the molar amounts of the lithium source, the precursor, and the dopant satisfy: M 1 / (Ni+Co+Mn) = 0-0.05; Li / (Ni+Co+Mn+M 1 = 1.3-1.5; wherein, the lithium source is calculated as Li, the precursor is calculated as the total molar amount of Ni, Co, and Mn, and the dopant is calculated as M 1 count.

22. The preparation method according to claim 21, wherein, The molar amounts of the lithium source, the precursor, and the dopant satisfy: M 1 / (Ni+Co+Mn) = 0.001-0.

03.

23. The preparation method according to claim 22, wherein, The molar amounts of the lithium source, the precursor, and the dopant satisfy: M 1 / (Ni+Co+Mn) = 0.002-0.

02.

24. The preparation method according to any one of claims 14-18, wherein, In step (2), the conditions for stage I include: heating rate < 8℃ / min; sintering temperature of 400-600℃; and holding time of 4-8 hours. The conditions for Stage II include: a heating rate of 0.5-5℃ / min; a sintering temperature of 750-950℃; and a holding time of 6-15 hours.

25. The preparation method according to claim 24, wherein, The conditions for stage I include: a heating rate of 1-7.5℃ / min; and a holding time of 5-7 hours. The conditions for Stage II include: a heating rate of 1-3℃ / min; a sintering temperature of 800-900℃; and a holding time of 8-10 hours.

26. The preparation method according to claim 24, wherein, In step (2), the average particle size D of the sintered product is... 50 It is 5-15μm.

27. The preparation method according to any one of claims 14-18, wherein, In step (3), the mixture further includes a coating agent, the coating agent being a mixture containing M 2 It contains at least one of the following: oxides, chlorides, sulfides, fluorides, hydroxides, hydroxy oxides, and carbonates.

28. The preparation method according to claim 27, wherein, The molar amount of the coating agent satisfies: M 2 / (Ni+Co+Mn+M 1 = 0-0.

05.

29. The preparation method according to claim 28, wherein, The molar amount of the coating agent satisfies: M 2 / (Ni+Co+Mn+M 1 = 0.001-0.

03.

30. The preparation method according to claim 29, wherein, The molar amount of the coating agent satisfies: M 2 / (Ni+Co+Mn+M 1 = 0.002-0.

02.

31. The preparation method according to any one of claims 14-18, wherein, In step (3), the conditions for the second sintering include: a sintering temperature of 300-750℃ and a sintering time of 6-10 hours.

32. A lithium-ion battery, characterized in that, The lithium-ion battery contains the lithium-rich manganese-based cathode material as described in any one of claims 1-13.

Citation Information

Patent Citations

  • Lithium ion battery positive electrode material modified by reactive melt infiltration and preparation method

    CN110380037A

  • High-power long-circulation nickel-cobalt-manganese ternary positive electrode material and preparation method thereof

    CN114824196A